Static site generators : why use them and how they work - Camden, Raymond (O'Reilly, 2015)
"For years now we've had powerful application servers like PHP, Node, and ColdFusion, that could create our web apps. But there has been a shift recently in terms of how much we do on an application server versus how much we can do on the browser itself, as well as how much is done on a mobile app instead. Static site generators provide a powerful middle ground between a full app server deployment and a simple collection of static files. In this webcast I'll talk about why you would use static site generators, how they work in general, how one (Harp) works in particular, and discuss how to add dynamic aspects back into the static site."--Resource description page.